NMD SERVER: NATURAL MEDICINES DATABASE FOR DRUG DISCOVERY - Kaushik, Aman Chandra; Sahi, Shakti (LIFE: International Journal of Health and Life-Sciences, 2017)
Cancer is the most frequently diagnosed disease globally and the second leading cause of the death. Natural Medicines are the alternative form of treatment that includes use of various plants. It is one of the safe treatment option to treat cancer and safer than allopathic medicines in order to reduce side effects. NMD Server: Natural Medicines Database for Drug Discovery is a unique and significant database of its kind, giving researchers, medical practitioners, pharmaceutical industries and students of Life Sciences an instant access to over 354 records of Natural Medicines which may be developed and used for treatment of Cancer. This database constitutes the specific information related to Natural Medicines and their respective target sites. NMD Server: Natural Medicines Database for Drug Discovery provides all the information (database fields) regarding the physiological parameters of database and is considered to be the linked table with pre-determined values and names that are included to aid in populating the fields of the linked tables. There have been many different types of fields with its respective data types that have been designated on the basis of data provided. NMDdock Tools have been integrated in this database for convenience for users like docking analysis of target and natural medicine, Sensitivity & Specificity analysis of natural medicine, Linear Correlation and Regression tool, Sequence Manipulation of target, Statistical Analysis. For the precise information about any particular drug, connectivity has been made with other databases and applications based highly bioinformatics tools have been embedded for convenience of users.